Effect of the incorporation of dehydrated cassava puree in the texture of pasta doughs - Monaca, Ana Belén (2023)
Fil: Monaca, Ana Belén. Universidad Nacional de Misiones. Facultad de Ciencias Exactas Químicas y Naturales; Argentina.